Family Culture in Dealing with Children with Autism Spectrum Disorder (Analytical Study) - Assaf, Mohammed; Al-Hayeh, Hassan (Journal of Educational Sciences, 2024)
The study aimed to understand the concept of family culture, identify the levels and dimensions of family culture in Palestine, as well as to recognize the reality of autism spectrum disorder in Palestine. Moreover, it aimed to understand how cultural interaction within the family affects the response of children with autism spectrum disorder to therapeutic interventions, and to propose a suggested framework for enhancing family culture in diagnosing autism spectrum disorder. The study adopted the descriptive-analytical approach according to the qualitative analysis model of the reality of family culture and autism spectrum disorder through relevant reports, statistics, and related studies. Among the most important findings of the study are: the family's role in positive family upbringing for children with autism spectrum disorder, understanding the proper upbringing skills for autistic children. It was found that there is a relationship between family culture and the treatment of autism spectrum disorder. Family culture is considered the foundation for diagnosing and treating children with autism spectrum disorder, by clarifying its role and responsibilities in dealing with autistic children, through finding creative solutions to communicate with the child, creating new alternatives to understand his behaviors, and engaging him in family activities, and interaction with others.